Optical Properties of Monocrystalline Silicon Nanowires - Gentsar, P.O.; Stronski, A.V.; Karachevtseva, L.A.; Onyshchenko , V.F. (Physics and Chemistry of Solid State, 2021)
The paper presents the results of a study of the optical reflection and transmission spectra of a silicon single crystal p-Si (100) with silicon nanowires grown on both sides and porous silicon p-Si (100) on a single crystal substrate in the spectral range 0.2 ÷ 1.7 μm. The layers of nanowires had a thickness of 5.5 µm, 20 µm, 50 µm and a porosity of 60 %. The porous silicon layers had a thickness of 5 μm, 50 μm and a porosity of 45 %, 55 % and 65 %. The change in the energy band structure in single-crystal silicon nanowires and in a single-crystal matrix of porous silicon is shown.